Redis 4.x Cookbook : Over 80 hand-picked recipes for effective Redis development and administration. - Huang, Pengcheng (Packt Publishing, 2018)
Redis is a popular key-value store database used commonly across many enterprises. Based on the latest version of Redis 4.x, this book provides useful recipes to help you overcome any obstacle when it comes to the different tasks associated with Redis - from working with data types to administering and troubleshooting your Redis solution.